Formulation of Alkaloid Loaded Phytosomes from Tinospora cordifolia and ex-vivo Intestinal Permeability Study - Thakur, Aishwarya Laxman; Patil, Kalpana Sabanna (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Phytosomes are newly introduced novel dosage form for improving the bioavailability and therapeutic effect of the herbal drug. The present study aimed to prepare and evaluate the alkaloid loaded phytosome from Tinospora cordifolia. Materials and Methods: Extracts were screened for total content of phenols, flavonoids and alkaloids. The prepared extract was further used for fractionation and dichloromethane fraction (F3) was used to prepare phytosomes. Phytosome was prepared by using thin film hydration method with different ratio of soya lecithin and cholesterol. The evaluation of phytosome was done by particle size and shape, polydispersity index, differential scanning calorimetry and fourier transfer infrared spectroscopy. Further, ex-vivo intestinal permeability study was performed for crude fraction and prepared phytosome to assess the intestinal permeability enhancement. Results: The all standardization parameters showed the results within the standard limits, thus confirming the quality and purity of raw material. The particle size and polydispersity index was found within the acceptable limits. The Differential scanning calorimetry and Fourier transfer infrared spectroscopy studies confirmed that there was no drug interaction with the excipients. The ex-vivo l permeable analysis of the intestines study was found that the phytosome shows enhancement in intestinal permeability than the crude alkaloid fraction. Conclusion: The above results indicated that the prepared alkaloid loaded phytosome shows promising potential in enhancement of intestinal permeability of Tinospora cordifolia
Keywords: Phytosomes; Tinospora cordifolia; Permeability; Soya lecithin; Cholesterol